Global health training and postgraduate medical education in Australia: the case for greater integration. Issue 6 (1st April 2013) - Mitchell, Rob D; Jamieson, Jennifer C; Parker, Jake; Hersch, Fred B; Wainer, Zoe; Moodie, A Rob
Summary: Global health (GH) training is well established overseas (particularly in North America) and reflects an increasing focus on social accountability in medical education. Despite significant interest among trainees, GH is poorly integrated with specialty training programs in Australia. While there are numerous benefits from international rotations in resource‐poor settings, there are also risks to the host community, trainee and training provider. Safe and effective placements rely on firm ethical foundations as well as strong and durable partnerships between Australian and overseas health services, educational institutions and GH agencies. More formal systems of GH training in Australia have the potential to produce fellows with the skills and knowledge necessary to engage in regional health challenges in a global context.